The Impact of Halal and Hygiene Certification on Consumption Levels with Trust as an Intervening Variable - Iffat, Muhammad Aidil; Imsar; Harahap , Muhammad Ikhsan (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
This research aimed to assess the impact of halal certification and hygiene on the consumption levels and trust of users of Garuda Indonesia and Aerofood ACS flight services. The study utilized multiple linear regression analysis, collecting data through questionnaires distributed to a sample of 96 Garuda Indonesia flight service users. The findings revealed that while halal certification did not significantly affect the level of consumer consumption of Aerofood ACS, it did have a significant impact on consumer trust. In contrast, hygiene was found to significantly influence both consumption levels and consumer trust. These results suggest that halal certification alone does not drive consumer consumption of Aerofood ACS products. Instead, hygiene plays a critical role in both enhancing consumption and building trust. Consequently, Aerofood ACS should focus on maintaining and improving product hygiene to better meet consumer expectations and increase consumption.